Children’s literature and hypermedia. The digitalization breakthrough in the children’s publishing sector - Baldini, Michela (Studi sulla Formazione/Open Journal of Education, 2019)
The paper aims to reflect on the parallelism between traditional and digital literature while analyzing the offer available on electronic market platforms. Taking into consideration adaptations of children's literature classics and original productions, such as enhanced books and apps, the paper purpose is to focus on interactivity and on the various degrees of involvement of the “digital reader” increasingly direct towards a prefigured visual narration.